2021
DOI: 10.1001/jamainternmed.2021.0036
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of Fish Consumption With Risk of Cardiovascular Disease and Mortality Among Individuals With or Without Vascular Disease From 58 Countries

Abstract: Mohan and Mente had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 49 publications
(97 reference statements)
5
60
0
1
Order By: Relevance
“…As in the present analysis, several large cohort studies have not been able to show any reduced mortality linked to frequent sh consumption (47,48). In line with our results, Engeset et al found a non-linear trend with fatty sh consumption and mortality in the European Prospective investigation into Cancer and Nutrition cohort, which included a part of our sample (48).…”
Section: Discussionsupporting
confidence: 86%
“…As in the present analysis, several large cohort studies have not been able to show any reduced mortality linked to frequent sh consumption (47,48). In line with our results, Engeset et al found a non-linear trend with fatty sh consumption and mortality in the European Prospective investigation into Cancer and Nutrition cohort, which included a part of our sample (48).…”
Section: Discussionsupporting
confidence: 86%
“…After screening the title and abstract, forty-five studies were selected for full-text evaluation. By full-text examination, twenty-five articles were eventually included for data synthesis with 2,027,512 participants and 103,734 CVD deaths [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies, involving 1,267,951 participants and 51,628 CVD deaths, investigated the association between the fish intake and the CVD mortality risk [ 13 , 14 , 15 , 16 , 17 , 18 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 40 ]. The pooled RR (95% CI) was 0.91 (0.85–0.98) for the highest versus the lowest fish consumption category (I 2 = 70.0%) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both food items have been independently associated with cardiovascular protection [ 40 , 41 ]. On one hand, a recent pooled analysis of data from four cohort studies indicates that a minimal fish intake of 175 g weekly is associated with lower risk of major CVD and mortality, specifically among patients with prior CVD [ 42 ]. These data are in line with the favorable effects of fish intake on CV outcomes observed in the only interventional study carried out so far, to the best of our knowledge, in patients with overt CVD [ 43 ].…”
Section: Discussionmentioning
confidence: 99%